Regulatory Sandboxes and Fintech Funding: Evidence from the UK - Cornelli, Giulio; Doerr, Sebastian; Gambacorta, Leonardo; Merrouche, Ouarda (Review of Finance, 2024)
Abstract Over fifty countries have introduced regulatory sandboxes to foster financial innovation. This article conducts the first evaluation of their ability to improve fintechs’ access to capital and attendant real effects. Exploiting the staggered introduction of the UK sandbox, we establish that firms entering the sandbox see an increase of 15% in capital raised post-entry. Their probability of raising capital increases by 50%. Sandbox entry also has a significant positive effect on survival rates and patenting. Investigating the mechanism, we present evidence consistent with lower asymmetric information and regulatory costs.